Calcareous Nannofossil Biostratigraphy and Biochronology at ODP Site 1123 (Offshore New Zealand): A Reference Section for the Last 20 Myr in the Southern Ocean - Agata Di Stefano; Natale Maria D’Andrea; Salvatore Distefano; Salvatore Urso; Laura Borzì; Niccolò Baldassini; Viviana Barbagallo (Journal of Marine Science and Engineering, 2023)
The quantitative analysis of the calcareous nannofossil content yield in the 600 m thick succession drilled at ODP Site 1123 (offshore New Zealand), considered as a reference section for the Southern Ocean region, allowed the recognition of 43 bioevents distributed along the last 20 Myr. The correlation with the excellent magnetostratigraphic record resulted in the attribution of numerical ages for the position of the detected horizons. Many of the marker species used in previous zonation were detected also at ODP Site 1123, but others revealed to be absent or of scarce applicability. On the other hand, the good applicability of additional events was verified and proved to be useful for the biostratigraphic subdivision and correlation. The obtained average bio- and chronostratigraphic resolution is about 0.6 Myr along the whole section, which increases to about 0.3 in the Pliocene–Holocene time interval. The final result is a detailed southern mid-to-high latitude nannofossil biochronology for the last 20 Myr, which confirms that the ODP Site 1123 succession represents a reference section for the Southern Ocean.